The complete mitochondrial genome of the file ramshorn snail Planorbella pilsbryi (Mollusca: Gastropoda: Hygrophila: Planorbidae) - Emma M. Rempel; Jeffrey M. Marcus; Jillian T. Detwiler (Mitochondrial DNA. Part B. Resources, 2021)
The file ramshorn snail Planorbella pilsbryi Baker, 1926 (Gastropoda: Hygrophila: Planorbidae) is a widespread herbivorous North American freshwater snail found in diverse habitats, including standing and moving water bodies. Genome skimming by Illumina sequencing allowed the assembly of a complete nuclear rRNA repeat sequence and a complete circular mitogenome of 13,720 bp from P. pilsbryi consisting of 75.3% AT nucleotides, 22 tRNAs, 13 protein-coding genes, 2 rRNAs and a control region in the typical order found in panpulmonate snails. Planorbella pilsbryi COXI features a rare TTG start codon while COXII, CYTB, ND2, ND3, and ND5 exhibit incomplete stop codons completed by the addition of 3′ A residues to the mRNA. Phylogenetic reconstruction of mitochondrial protein-coding gene and rRNA sequences places P. pilsbryi as sister taxon to Planorbella duryi (Planorbidae) within family Planorbidae, which is consistent with previous phylogenetic hypotheses.